Indigenous Abolition and the Third Space of Indian Child Welfare - Theresa Ysabel Rocha Beardall (Genealogy, 2025)
This article introduces the Third Space of Indian child welfare to theorize how Indigenous nations simultaneously engage and disrupt settler legal systems while building sovereign, care-based alternatives. Drawing from legal analysis, Indigenous political thought, and sociohistorical synthesis, I trace the historical continuity from boarding schools to today’s foster care removals, showing how child welfare operates as a colonial apparatus of family separation. In response, Native nations enact governance through three interrelated strategies: strategic legal engagement, kinship-based care, and tribally controlled family collectives. Building on Bruyneel’s theory of third space sovereignty, Simpson’s nested sovereignty, and Lightfoot’s global Indigenous rights framework, I conceptualize the Third Space as a dynamic field of Indigenous governance that transcends binary settler logics. These practices constitute sovereign abolitionist praxis. They reclaim kinship, resist carceral systems, and build collective futures beyond settler rule. Thus, rather than treating the Indian Child Welfare Act (ICWA) as a federal safeguard, I argue that tribes have repurposed ICWA as a legal and political vehicle for relational governance. This reframing challenges dominant crisis-based narratives and positions Indigenous child welfare as the center of a “global Indigenous politics of care” with implications for theories of sovereignty, family, and abolitionist futures across disciplines, geographies, and social groups. The article concludes by reflecting on the broader implications of the Third Space for other Indigenous and minoritized communities navigating state control and asserting self-determined care.